Bradycardia-dependent interatrial block with retrograde left atrial activation. Issue 2 (February 1977) - Sobrino, J A; del Rio, A; Maté, I; Sobrino, N
Abstract : A patient with a peculiar interatrial block is reported. The electrocardiogram showed a short PR interval and negative P waves in II, III, and aVF, which were preceded, 0-07 s earlier, by another positive P wave present in the right praecordial leads which were absent in the limb leads. From the study with His bundle electrograms, high right atrial electrograms, and bipolar oesophageal electrocardiograms, it could be proved that atrioventricular, His-Purkinje, and right intra-atrial conduction were normal, and that P waves recorded in limb leads represented left atrial depolarization; whereas the ones in the right praecordial leads corresponded to right atrial activation. The vectorial analysis from both P waves and atrial potentials showed that the left atrium was activated in a retrograde fashion, because of an interatrial block. This block was bradycardia dependent and it disappeared in the cycles shorter than 800 ms.